2020
DOI: 10.1097/jp9.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

Total pancreatectomy with islet autotransplantation in diabetic and pre-diabetic patients with intractable chronic pancreatitis

Abstract: Total pancreatectomy with islet autotransplantation (TPIAT) is an effective treatment option for non-diabetic patients with intractable chronic pancreatitis. The outcome and potential benefits for pre-diabetic and diabetic patients are less well established. Thirty-four patients underwent TPIAT were retrospectively divided into 3 groups according to pre-operative glycemic control: diabetes mellitus (DM) (n=5, 15%), pre-DM (n=11, 32%) and non-DM (n=18, 54%). Pre-operative fasting c-peptide was detectable and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Although there is a substantial overlap on baseline measures between the groups who were insulin independent and dependent, our results are consistent with other recent studies 33,39 showing that having abnormal glycemia (prediabetes HbA1c or fasting blood glucose levels) appears to convey a very high likelihood for an individual patient to remain insulin dependent after surgery (Figure 2), and thus proceeding to surgery before progression to prediabetes is likely desirable. Recipients with high BMI, high stimulated blood glucose levels, or low estimated IEQs/kg (<2500 IEQs/kg) also appeared to have a low likelihood of insulin independence, and these measures could also be signs for poor metabolic outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Although there is a substantial overlap on baseline measures between the groups who were insulin independent and dependent, our results are consistent with other recent studies 33,39 showing that having abnormal glycemia (prediabetes HbA1c or fasting blood glucose levels) appears to convey a very high likelihood for an individual patient to remain insulin dependent after surgery (Figure 2), and thus proceeding to surgery before progression to prediabetes is likely desirable. Recipients with high BMI, high stimulated blood glucose levels, or low estimated IEQs/kg (<2500 IEQs/kg) also appeared to have a low likelihood of insulin independence, and these measures could also be signs for poor metabolic outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with diabetes or prediabetes before TPIAT have been shown to have fewer isolated and transplanted islets and worse metabolic outcomes than preoperative nondiabetics. 14 Similarly, we found that patients with preoperative diabetes yielded lower IEQ than nondiabetic patients, although this was only statistically significant in the intraoperative group. One year fasting, C-peptides were also lower in preoperative diabetics than nondiabetics; however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 51%
“…Gradually, emphasis shifted from insulin independence to better control of DM and avoiding the subsequent brittleness [ 12 ]. Recently, there have been reports of this procedure offered to current diabetic patients showing advantages in management [ 13 ].…”
Section: Advances In Indicationsmentioning
confidence: 99%
“…The presence of pre-diabetes defined by the American Diabetic Association (fasting plasma glucose between 100 and 125 mg/dl (5.6–6.9 mmol/L) or HbA1c between 5.7% and 6.4% without any pharmacological support), was correlated with a significantly lower chance for insulin independence at 1 year, 13% vs. 53% in patients with normal glucose control, which has major clinical implications. Information about HbA1c and fasting blood glucose are easily obtained to help in preoperative decisions and set up realistic expectations about glucose control postoperatively [ 13 ].…”
Section: Advances In Evaluationmentioning
confidence: 99%